Revascularisation or medical therapy in elderly patients with acute anginal syndromes: the RINCAL randomised trial - Adam de Belder; Aung Myat; Jonathan Blaxill; Peter Haworth; Peter O’Kane; Robert Hatrick; Rajesh Aggarwal; Andrew Davie; William Smith; Robert Gerber; Jonathan Byrne; Dawn Adamson; et al. (2021)
Background: Historically the elderly have been under-represented in non-ST-elevation myocardial infarction (NSTEMI) management trials. Aims: The aim of this trial was to demonstrate that an intervention-guided strategy is superior to optimal medical therapy (OMT) alone for treating NSTEMI in elderly individuals. Methods: Patients (≥80 years, chest pain, ischaemic ECG, and elevated troponin) were randomised 1:1 to an intervention-guided strategy plus OMT versus OMT alone. The primary endpoint was a composite of all-cause mortality and non-fatal myocardial reinfarction at 1 year. Ethics approval was obtained by the institutional review board of every recruiting centre. Results: From May 2014 to September 2018, 251 patients (n=125 invasive vs n=126 conservative) were enrolled. Almost 50% of participants were female. The trial was terminated prematurely due to slow recruitment. A Kaplan-Meier estimate of event-free survival revealed no difference in the primary endpoint at 1 year (invasive 18.5% [23/124] vs conservative 22.2% [28/126]; p=0.39). No significant difference persisted after Cox proportional hazards regression analysis (hazard ratio 0.79, 95% confidence interval 0.45-1.35; p=0.39). There was greater freedom from angina at 3 months (p<0.001) after early intervention but this was similar at 1 year. Both non-fatal reinfarction (invasive 9.7% [12/124] vs conservative 14.3% [18/126]; p=0.22) and unplanned revascularisation (invasive 1.6% [2/124] vs conservative 6.4% [8/126]; p=0.10) occurred more frequently in the OMT alone cohort. Conclusions: An intervention-guided strategy was not superior to OMT alone to treat very elderly NSTEMI patients. The trial was underpowered to demonstrate this definitively. Early intervention resulted in fewer cases of reinfarction and unplanned revascularisation but did not improve survival.